Novel Unilateral Dental Expander Appliance (UDEX): A Compound Innovative Materials - Hasan, Hasan Sabah; Abdallah, Abdallah A.; Khan, Imran; Alosman, Hala Sadek; Kolemen, Ayshan; Alhayani, Bilal (TECH SCIENCE PRESS, 2021)
True unilateral posterior crossbite in adults is a challenging maloc-clusion to treat, especially when we need to correct cross-arch segments with unwanted effects on non-cross segments. Conventional expansion methods are expected to have some shortcomings; the Unilateral dental expander appliance used to restore unilateral cross bite dental arch is an uncommon appliance; for this, a designed new device is needed. This paper aimed to invite a new unilateral dental expander appliance (UDEX) to treat unilateral dental poste-rior crossbite in adults using available dental material, easy to use and handle, well tolerated by the patient, and biocompatible with oral structure. It could find that in all dental markets and dental clinics-an eighteen-year-old female with bilateral crossbite and upper and lower dental arch crowding. During active orthodontic treatment, a quad-helix expander had broken from one side at soldering between band and wire attachment. The patient did not show up to the clinic for a while due to COVID 19 pandemic lockdown, leading to a true unilateral crossbite at the dental arch's upper left side, especially at the molar premolars area. This unilateral cross bite was treated using a new specially designed expanded appliance as a unilateral posterior cross bite dental maxillary expander. As a result of this study, orthodontic treat-ment was finished within (15) months, much less than expected. We obtained Class I molar and canine relationships with uncrossed dental arches in both upper arch sides, proper overbite and overjet with well-leveled and aligned teeth as it confirmed by clinical examination and radiographic images (OPG (Orthopantomogram) and cephalometric radiograph (WebCeph analysis digi-talized computer program). Conclude from that, the newly designed unilateral dental expander (UDEX) is proven to be useful for treating real unilateral pos-terior crossbites as single molar or premolar tooth and multiple joint unilateral crossed posterior teeth. Also, it could easily modify it for future unilateral crossed purposes. This appliance was fabricated using readily available dental material, well tolerated by patients, and reduced the need for excessive patient compliance. An orthodontist could fabricate devices, or cautious laboratory work is required; it can rapidly achieve favorable results.
Keywords: Unilateral crossbite; dental material; acrylic pads; wire bending; expander; QUAD-HELIX; Computer Science; Materials Science